Estimation of central tendency, dispersions and correlations of growth traits in Rambouillet sheep (Indian Journal of Animal Production and Management, 2016)
Data on growth traits of 7161 animals used in present study were collected from the history sheets of  Rambouillet sheep maintained at Government Sheep Breeding Farm, Reasi, J&K, India. Growth traits  included in the study were birth weight (BW), three-month weight (3MW), six-month body weight (6MW),  nine-month body weight (9MW) and twelve-month body weight or yearling weight (YW). The average  weight gain of individual during 0-3 months (ADG1), 3-6 months (ADG2), 6-9 months (ADG3), 9-12  months (ADG4) and 3-12 months (ADG5) were calculated as weight gain during particular period divided  by duration of that period in days. The overall averages were 3.39±0.01kg, 14.16±0.03kg, 19.59±0.04kg,  24.85±0.05kg and 28.71±0.06kg, respectively for BW, 3MW, 6MW, 9MW and YW. The overall averages  were 0.119±0.002kg, 0.071±0.001kg, 0.058±0.006kg, 0.056±0.001kg and 0.054±0.001kg, respectively for  ADG1, ADG2, ADG3, ADG4 and ADG5. Sex had significant effect on all growth traits under study except  for 9 MW, where sex had non-significant. For growth rate traits sex had non-significant effect for ADG1 and  ADG4. The correlation coefficients of between different body weights and average daily weight gain ranges  from -0.040±0.01 between ADG1 & ADG5 to 0.97±0.01 between BW and 9W. Most of the correlations  values were highly significant barring few exceptions, which indicate improvement of one trait will result  in improvement of other traits also. Low to medium coefficient of variations (CV) for growth traits indicate  collateral selection will be effective for improvement of growth traits.
Keywords: Co-efficient of variations; Correlations; Growth rate; Growth traits; Rambouillet